A Prospective Study of Immune Response After COVID-19 or Vaccination and Correlation Between Avidity Index and Neutralizing Capacity - Emma Löfström; Anna Eringfält; Arne Kötz; Wanda Christ; Stefan Kunkel; Johan Tham; Jonas Klingström; Johan Undén (Advances in Virology)
Conclusion: Anti-spike IgG levels can be used as an estimation of the neutralizing titer, with the avidity index not contributing to a better estimation. There is a stronger initial immune response after vaccination, compared with natural infection. However, specific antibody levels decline over time, highlighting the importance of vaccine boosters.